Gesture Facilitates the Syntactic Analysis of Speech - Holle, Henning; Obermeier, Christian; Schmidt-Kassow, Maren; Friederici, Angela D.; Ward, Jamie; Gunter, Thomas C. (Frontiers in Psychology, 2012)
Recent research suggests that the brain routinely binds together information from gesture and speech. However, most of this research focused on the integration of representational gestures with the semantic content of speech. Much less is known about how other aspects of gesture, such as emphasis, influence the interpretation of the syntactic relations in a spoken message. Here, we investigated whether beat gestures alter which syntactic structure is assigned to ambiguous spoken German sentences. The P600 component of the Event Related Brain Potential indicated that the more complex syntactic structure is easier to process when the speaker emphasizes the subject of a sentence with a beat. Thus, a simple flick of the hand can change our interpretation of who has been doing what to whom in a spoken sentence. We conclude that gestures and speech are an integrated system. Unlike previous studies, which have shown that the brain effortlessly integrates semantic information from gesture and speech, our study is the first to demonstrate that this integration also occurs for syntactic information. Moreover, the effect appears to be gesture-specific and was not found for other stimuli that draw attention to certain parts of speech, including prosodic emphasis, or a moving visual stimulus with the same trajectory as the gesture. This suggests that only visual emphasis produced with a communicative intention in mind (that is, beat gestures) influences language comprehension, but not a simple visual movement lacking such an intention.